The Use of MALDI-TOF MS as a Diagnostic Tool for Adult Trichuris Species - Rivero, Julia; Zurita, Antonio; Cutillas, Cristina; Callejón, Rocío (Frontiers in Veterinary Science, 2022)
Trichuriasis is considered a Neglected Tropical Disease, being the second most common helminthiasis in humans. Detection of Trichuris in routine diagnosis is usually done by microscopic detection of eggs in fecal samples. Other molecular analyses are more reliable and could be used, but these analyses are not routinely available in clinical microbiology laboratories. The use of matrix-assisted laser desorption/ionization-time of flight (MALDI-TOF) mass spectrometry (MS) is increasing since the last decades due to its recent evidence as a potential role for reliable identification of microorganisms and a few nematodes. But, for parasites detection, normalized protocols and the acquisition and introduction of new species to the database are required. We carried out a preliminary study confirming the usefulness of MALDI-TOF MS for the rapid and reliable identification of Trichuris suis used as control and the creation of an internal database. To create main spectra profiles (MSPs), the different parts of five whipworms (esophagus and intestine) were used, developing different tests to verify the repeatability and reproducibility of the spectra. Thus, to validate the new internal database, 20 whipworms, separating the esophagus and intestine, were used, of which 100% were accurately identified as T. suis, but could not distinguish between both parts of the worm. Log score values ranged between 1.84 and 2.36, meaning a high-quality identification. The results confirmed that MALDI-TOF MS was able to identify Trichuris species. Additionally, a MALDI-TOF MS profile of T. suis proteome was carried out to develop a first internal database of spectra for the diagnosis of trichuriasis and other Trichuris spp.